Aggregate productivity slowdown in Europe: New evidence from corporate balance sheets - Laurent Maurin; Marcin Wolski (European Investment Bank (EIB), 2021)
Capitalising on the productivity decomposition proposed by Olley and Pakes (1996), we analyse the role of financial factors behind the relatively muted post-crisis rebound in productivity compared to previous upturns in Europe. Firstly, we provide an OLS-consistent framework to decompose sector-level productivity into trend and allocative efficiency components. We then extend our approach to estimate the contribution of firm-level confounders to the sector-level allocative component. Secondly, we find that financial leverage played an important role in explaining the change in aggregate productivity growth in Europe between 2004 and 2017. Thirdly, focusing on Northern and Western Europe, we show that the productivity potential could not be fully exploited due to access to credit conditions. Specifically, reducing collateral bottlenecks could more than double the effectiveness of financial leverage in spurring productivity growth in this region between 2014-17.
Keywords: 330